Development of the First Oral Bioprecursors of Bis‐alkylguanidine Antimalarial Drugs. Issue 2 (8th January 2014) - Degardin, Mélissa; Wein, Sharon; Duckert, Jean‐Frédéric; Maynadier, Marjorie; Guy, Alexandre; Durand, Thierry; Escale, Roger; Vial, Henri; Vo‐Hoang, Yen
Abstract Plasmodium falciparum is responsible of the most severe form of malaria, and new targets and novel chemotherapeutic scaffolds are needed to fight emerging multidrug‐resistant strains of this parasite. Bis‐alkylguanidines have been designed to mimic choline, resulting in the inhibition of plasmodial de novo phosphatidylcholine biosynthesis. Despite potent in vitro antiplasmodial and in vivo antimalarial activities, a major drawback of these compounds for further clinical development is their low oral bioavailability. To solve this issue, various modulations were performed on bis‐alkylguanidines. The introduction of N‐disubstituents on the guanidino motif improved both in vitro and in vivo activities. On the other hand, in vivo pharmacological evaluation in a mouse model showed that the N‐hydroxylated derivatives constitute the first oral bioprecursors in bis‐alkylguanidine series. This study paves the way for bis‐alkylguanidine‐based oral antimalarial agents targeting plasmodial phospholipid metabolism.